O LIVRO E OS RECURSOS DIDÁTICOS NO ENSINO DE MATEMÁTICA - Ramos, Fernando Carvalho (2006)
The study analyzes the books of Mathematics related in the GUIDE OF DIDACTIC BOOKS OF MATHEMATICS 2005 (5th to 8th grades of Elementary School) of the National Program of Didactics Books (PNLD) in what refers to citations of didactic resources (RD) and its job in the teaching-learning process. After the standardization of the concept of didactic resources, the materials cited in the selected books had been related and confectioned to verify their practicality. The Evaluation Fiche attached to the GUIDE was analyzed towards its demanding concerning indications of inserted didactic resources in books approved by PNLD. The analysis of books was carried through by means of the fulfilling of a bibliographical fiche for each of the 92 (ninety two) books object of the study. From these procedures other types of didactic resources not indicated by the books of the sample of the inquiry had been related and that consist in books not selected by the PNLD and in educational sites. The results of the inquiry demonstrate that: a) the presence of didactic resources in books elapses of the qualification and competence of its authors, once that as well as the concept as the requirement of RD are not clearly defined by the National Curricular Parameters (PCNs) and by the PNLD and, b) the didactic book needs to offer to the professor, besides the content of quality, written in clear and precise language didactic resources, basic and complementary bibliography (for the professor and the pupil), orientations and suggestions of didactic activities (individually and in groups), as well as pedagogical procedures for the adaptation of the contents, activities and RD to the specific environments of learning and indications for the accompaniment of the progress of the pupil.